Quantitative Analysis of Oxide Growth During Ti Galvanostatic Anodization. Issue 11 (6th July 2020) - Zhang, Zhaoying; Liu, Qianqian; He, Mingfei; Tang, Fengrui; Ying, Zongrong; Xu, Haoqing; Song, Ye; Zhu, Junwu; Zhu, Xufei
Abstract : The mechanism of TiO2 nanotubes has attracted increasing attention. However, relationships between the anodizing parameters and nanotube size (or oxide volume) have been rarely studied. The traditional field-assisted dissolution theory can only qualitatively explain the cause of the pore formation but cannot quantitatively explain the relationship between the growth height of nanotubes and the anodizing current. Here, the growing processes of TiO2 nanotubes in four current at three different NH4 F concentrations were carefully studied. Experimental results contradicting the traditional dissolution theory were found. Considering that the height of the nanotubes does not fully reflect oxide growth, the volume of growing oxide was studied for the first time. The results show that the oxide volume decreases while the pore volume increases with the increase of the concentration of NH4 F in the process of constant current anodization. However, the sum of the two volumes was approximately a fixed value under the same current. The sum of the oxide volume and the pore volume increases with the increase of the anodizing current, regardless of the concentration of ammonium fluoride. It means that the growth height of nanotubes has nothing to do with the concentration of NH4 F, which is against the field-assisted dissolution theory.